2011
DOI: 10.5606/tjr.2011.004
|View full text |Cite
|
Sign up to set email alerts
|

Ten Year Results of a Fibromyalgia Out-Patient Clinic: Is There a Happy Ending?

Abstract: Amaç: Bu geriye dönük özdeş grup çalışmasında, fibromiyalji sendromlu (FMS) hastaların klinik özellikleri, tedavi seçenekleri ve sonuçları belirlendi ve Fibromiyalji İzlem Polikliniğimizde (FİP) edinilen 10 yıllık deneyimlerin sonuçları sunuldu. Hastalar ve yöntemler: Fibromiyalji sendromu şüphesi ile FİP'ye sevk edilen 308 hastanın (247 kadın, 61 erkek) 252'sine FMS tanısı konuldu. Tüm hastaların demografik verileri kaydedildi. Fibromiyalji izlem polikliniği'nin hasta formları kullanılarak hastalarda yaygın v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…In previous studies, it has been recommended that predominant symptoms must be taken into consideration when developing a treatment plan, as FMS has a heterogeneous nature causing difficulties in diagnosis and treatment. 1 In accordance with this recommendation and our study results, it can be suggested that H. pylori eradication is not enough to resolve all symptoms of fibromyalgia, however, it may be an effective treatment if the predominant symptom is pain.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In previous studies, it has been recommended that predominant symptoms must be taken into consideration when developing a treatment plan, as FMS has a heterogeneous nature causing difficulties in diagnosis and treatment. 1 In accordance with this recommendation and our study results, it can be suggested that H. pylori eradication is not enough to resolve all symptoms of fibromyalgia, however, it may be an effective treatment if the predominant symptom is pain.…”
Section: Discussionsupporting
confidence: 70%
“…1 Sleep disturbance is one of the most common symptoms of FMS. 2 Fibromyalgia is frequently found to comorbid with depression and anxiety.…”
Section: ©2014 Turkish League Against Rheumatism All Rights Reservedmentioning
confidence: 99%